Displaced Colles fractures: Functional outcome following closed reduction and stabilization with percutaneous K-wires - Manandhar, RR; Lakhey, S; Pandey, BK; Pradhan, RL; Sharma, S; Rijal, KP (Nepal Orthopaedic Association Journal, 2013)
Background: Displaced Colles fractures are generally treated by manipulation and below elbow cast application. Malunion is a common complication resulting in pain, mid carpal instability and post-traumatic arthritis. Fracture stabilization by percutaneous pinning is a simple, minimally invasive technique which helps prevent dislodgment of the fracture thereby minimizing complications. The study aims to assess the amount of collapse after closed manipulation and percutaneous pinning with K-wires and its correlation with the functional outcome of the wrist after union. Methods: A prospective study was conducted from October 2006 to November 2009. Fifty adults (27 female, 23 male) with an average age of 40.72 years with type II fractures underwent closed manipulation and percutaneous pinning with crossed K-wires as the primary procedure. Serial radiographs were taken to document the amount of collapse. The functional outcome was assessed using Mayo Wrist Score. Results: At the final follow up of 6 months the collapse in the mean dorsal angle was 1.15 and mean ulnar variance 0.51. Functionally 25 patients (53.19%) had excellent, 17 patients (36.17%) good and 5 patients (10.63%) had satisfactory or fair outcome. Conclusions: Displaced Colles fractures should be reduced and stabilized with percutaneous K-wires to achieve an excellent functional outcome. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8135 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 14-20